Extremism, Radicalism and Radicalization A necessary distinction in the terrorism debate - Sitoe, Rufino (2022)
This article makes a conceptual debate on terrorism, extremism, radicalism and radicalization with the aim of producing distinctions that enrich the theoretical debate on the terrorist phenomenon, as it assumes that there are rhetorical traps that need to be clarified and overcome in order to improve the debate and theorization about the terrorism. For this purpose, the main methodology used was a qualitative approach, supported by bibliographic and documentary techniques, through which the main literature on the concepts was consulted, as well as documents from national and international institutions and organizations that deal with the phenomena under analysis. The main conclusion produced is that these four concepts are distinct from each other because terrorism is essentially a violent action carried out by individuals, groups, or even by States, against certain civilian targets with the intention of reaching a larger audience than the immediate victims, with a specific political objective; in turn, extremism refers to violent or non-violent intolerance of others based on the conviction of the assertiveness of one’s beliefs and consequent attempt to restrict the freedom of others to think and act; while radicalism represents a progressive thought that consists of the struggle for rights and freedoms of traditionally excluded groups and; finally, radicalization is the process that an individual goes through until the decision to commit terrorist acts. As a result, extremism is part of the process of radicalization and terrorism is an action resulting from radicalization. Radicalism is a concept more distant from the others due to its positive connotation in social transformation.